Effect of Cultivation Methods and Nitrogen Application Timings on Root Morphology of Lowland Rice Variety - Gunarathna, Morawaka K.J.C. Kumari; Datta, Avishek; Anal, Anil Kumar; Kuwornu, John K. M. (Pathum Thani : Asian Institute of Technology, 2018)
With increasing population and limitations of food, many researchers are looking into various methods to improve rice yield with less usage of resources. Unfortunately, most of the farmers still use conventional methods to cultivate rice, which require high amount of resources and that led to losses. This study is focused to overcome this issue by achieving three objectives, to determine the effect of split nitrogen application on the root characteristics of rice, determine the effect of different cultivation methods on the root characteristics of rice and evaluate the interaction effect of split nitrogen application and different cultivation methods on the root characteristics. Analysis of variance shows that only split nitrogen application had a significant effect on root system development, but cultivation methods did not have any interaction lowland rice variety (RD 57). Root system parameters were depended on split nitrogen application and the best method was to split the fertilizer application as basal, active tillering, panicle initiation and flowering stages. The study provides useful insights to develop split nitrogen application for lowland rice.
A capstone project report submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Engineering Biosystems Engineering
Capstone Project (B.Sc.)-Asian Institute of Technology, 2018
Keywords: Split nitrogen applications; Cultivation methods; RD 57; Root traits